Using strategic communities to foster inter-organizational collaboration. Issue 6 (3rd October 2016) - Audet, Madeleine; Roy, Mario
Abstract : Purpose: The purpose of this paper is: to report on an experiment in building up inter-organizational collaboration between healthcare organizations; and to identify how structure and some of the components of the strategic community (SC) approach to organizational change can have a long-term impact on inter-organizational collaboration. Design/methodology/approach: This paper resulted from participative action-research held from 2007 to 2013. A systematic collection of data (field notes, 746 hours of observations, proceedings, 186 interviews, journals, focus groups, discussion forums) was conducted in the various cycles of the action-research. Findings: Adapted to the healthcare sector, the SC has taken the form of a temporary inter-organizational collaboration structure composed of health professionals, first-level managers, general practitioners, specialized doctors, and non-profit organization representatives. The SC approach appeared to be an efficient strategy for taking action. Practical implications: The SC approach appeared to be appropriate for cases where the inter-organizational collaboration had clearly declined, where several other attempts had failed, and where the care trajectory involved vulnerable clients who had to travel between different service points for the required care. Originality/value: This study illustrates how SC helps to significantly improve inter-organizational collaboration in the healthcare sector. It likewise acknowledges the relevance of Thomson and Perry's (2006) work in analyzing and emphasizing the dimensions required to ensure successful inter-organizational collaboration.